Insight into molecular and rheological properties of sprouted sorghum flour. (15th September 2021) - Marchini, Mia; Arduini, Riccardo; Carini, Eleonora
Highlights: Sprouting affects molecular properties of sorghum-water systems. Sprouting does not affect viscoelasticity of sorghum-water systems. The use of flour from sprouted sorghum is encouraged for food development (e.g., flat bread). Abstract: This work investigated the effect of sprouting and drying post-sprouting on technological functionalities of sorghum flour as probed by Low-resolution Proton Nuclear Magnetic Resonance ( 1 H NMR) and Dynamic Mechanical Analysis (DMA). Multivariate statistics were used to assess the effect of flour (from sprouted and unsprouted sorghum, and wholewheat) and hydration level on flour–water systems molecular and viscoelastic properties. Overall, sorghum-based systems showed greater molecular mobility explaining poorer viscoelastic properties than those obtained from wheat. Sprouting affected the molecular properties of sorghum flour–water systems, while no differences were observed in the two sprouted samples dried in different conditions. However, sprouting did not affect the viscoelastic properties of sorghum-water systems. These results bolster the use of sprouted sorghum in composite flours for the development of sustainable finished products with high nutritional value and satisfactory technological and organoleptic properties.